The impact of promotional strategies toward customer awareness on the use of bankislam.SMS / Zarina Bahauddin - Bahauddin, Zarina (Faculty of Business and Management, 2005)
This research was conducted to identify whether the promotional strategies implemented by Bank Islam Malaysia Berhad is effective or not, in order to enhance public awareness towards its new service namely,bankislam.SMS. The main objective of this research is to know the level of public awareness and use of bankislam.sms new service by Bank Islam Malaysia Berhad. Promotion is important in informing, persuading, and reminding customers about particular product or service offered by the company. By using promotion, it is able to attract customer's attention and influence them to make a purchase or use the service. There are several techniques that have been used in order to obtain information from the respondents. The targeted respondents for this research were located in Bandar Wawasan BIMB branch. 100 questionnaires had been distributed to those respondents and only 75 questionnaires were accepted after screening. Furthermore, secondary data from sources such as internal BIMB data and fact, printed media, Internets and articles were used in the research in order to obtain further, current and in depth information about the study. From the findings, it is found that promotional strategies undertaken by BIMB just in moderate level. BIMB staffs are ranking the most effective tools compared to others. Generally, the study shows that 85.3% of respondents are aware with the bank's new service but the percentage of those using this service is quite low at 29%. Thus, the promotional activities implemented by Bank Islam Malaysia Berhad need to be improved from time to time in order to enhance public awareness and encouraged them to use bankislam.SMS in conducting their banking transactions. The success of the promotional activities needs a full commitment, sustained attention and interaction, support and effort from all of the BIMB staffs because all of them are depending on each other to achieve their mission and objective for the company and thus, continue surviving in their long-term operation. In conclusion for the overall research, the company still needs some improvement especially in term of promotional tools and advertising media used to ensure all the customers of BIMB aware and use bankislam.SMS service.